Development of a multiplex polymerase chain reaction‐sequence‐specific primer method for NKG2D and NKG2F single‐nucleotide polymorphism typing using isothermal multiple displacement amplification products. Issue 6 (27th March 2013) - Kaewmanee, M.; Phoksawat, W.; Romphruk, A.; Romphruk, A. V.; Jumnainsong, A.; Leelayuwat, C.
Abstract: Natural killer group 2 member D (NKG2D) on immune effector cells recognizes multiple stress‐inducible ligands. NKG2D single‐nucleotide polymorphism (SNP) haplotypes were related to the levels of cytotoxic activity of peripheral blood mononuclear cells. Indeed, these polymorphisms were also located in NKG2F . Isothermal multiple displacement amplification (IMDA) is used for whole genome amplification (WGA) that can amplify very small genomic DNA templates into microgram with whole genome coverage. This is particularly useful in the cases of limited amount of valuable DNA samples requiring multi‐locus genotyping. In this study, we evaluated the quality and applicability of IMDA to genetic studies in terms of sensitivity, efficiency of IMDA re‐amplification and stability of IMDA products. The smallest amount of DNA to be effectively amplified by IMDA was 200 pg yielding final DNA of approximately 16 µg within 1.5 h. IMDA could be re‐amplified only once (second round of amplification), and could be kept for 5 months at 4°C and more than a year at −20°C without loosing genome coverage. The amplified products were used successfully to setup a multiplex polymerase chain reaction‐sequence‐specific primer for SNP typing of the NKG2D/F genes. The NKG2D/F multiplex polymerase chain reaction (PCR) contained six PCR mixtures for detecting 10 selected SNPs, including 8 NKG2D/F SNP haplotypes and 2 additional NKG2D coding SNPs. This typing procedure will be applicable in both clinical and research laboratories. Thus, our data provide useful information and limitations for utilization of genome‐wide amplification using IMDA and its application for multiplex NKG2D/F typing.